Resgate da minha vida, minha história - Miquiles, Gracimar da Paz (Brasil, 2024)
This work addresses the author's academic and practical training journey in the Bachelor of Pedagogy program, focusing on experiences gained during internships in Early Childhood Education, Elementary Education, and School Management. The work explores the knowledge acquired and challenges faced throughout the internships, highlighting the practical application of theoretical knowledge and everyday school experiences. In Early Childhood Education, the emphasis was on playfulness and affectivity practices, essential for children's development. In Elementary Education, the author dealt with age diversity, emphasizing the importance of interdisciplinarity and content contextualization. In School Management, the complexity of the manager's role and the importance of teamwork for administrative efficiency and educational success were discussed. To facilitate understanding of the topics, the work is divided into three chapters, addressing the educational journey, professional trajectory, and experiences and learnings from course activities and Pedagogy internships.